Does cochlear implantation and electrical stimulation affect residual hair cells and spiral ganglion neurons? - Coco, Anne (2006)
Increasing numbers of cochlear implant subjects have some level of residual hearing at the time of implantation. The present study examined whether (i) hair cells that have survived one pathological insult (aminoglycoside deafening), can survive and function following long-term cochlear implantation and electrical stimulation (ES); and (ii) chronic ES in these cochleae results in greater trophic support of spiral ganglion neurons (SGNs) compared with cochleae devoid of hair cells. Eight cats, with either partial (n=4) or severe (n=4) sensorineural hearing loss, were bilaterally implanted with scala tympani electrode arrays 2 months after deafening, and received unilateral ES using charge balanced biphasic current pulses for periods of up to 235 days. Frequency-specific compound action potentials and click-evoked auditory brainstem responses (ABRs) were recorded periodically to monitor the residual acoustic hearing. Electrically-evoked ABRs (EABRs) were recorded to confirm the stimulus levels were 3-6 dB above the EABR threshold. On completion of the ES program the cochleae were examined histologically. Partially deafened animals showed no significant increase in acoustic thresholds over the implantation period. Moreover, chronic ES of an electrode array located in the base of the cochlea did not adversely affect hair cells in the middle or apical turns. There was evidence of a small but statistically significant rescue of SGNs in the middle and apical turns of stimulated cochleae in animals with partial hearing. Chronic ES did not, however, prevent a reduction in SGN density for the severely deaf cohort, although SGNs adjacent to the stimulating electrodes did exhibit a significant increase in soma area (p<0.01). In sum, chronic ES in partial hearing animals does not adversely affect functioning residual hair cells apical to the electrode array. Moreover, while there is an increase in the soma area of SGNs close to the stimulating electrodes in severely deaf cochleae, this trophic effect does not result in increased SGN survival.